(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Article relates to the field of comparative religion. It opens up the history of the Muslim and Christian fasting rules, similarities and differences of the ritual in the two religions. Also explains the ritual of fasting as means of moral and physical purification, penance for sins, calling for compassion towards others.